PERANAN ADAT DAYAK KENINJAL DAN MELAYU DALAM PENGELOLAAN KONFLIK SUMBER DAYA ALAM DI WILAYAH TANAH PINOH KABUPATEN MELAWI - Kristianus (JURNAL BORNEO AKCAYA, 2016)
The title of this study is The Role of Customs Dayak Keninjal and Melayu in the Conflict Management of Natural Resources in the Tanah Pinoh Melawi. This study was conducted using a combination of quantitative and qualitative methods. Data collection tools such as questionnaires and interview guides. The study was conducted during three months in 2015. An important finding of this study is that the population in the district of Tanah Pinoh majority is Dayak Keninjal and Malay. The role of customs is still quite important as the norm will be retained in regulating social life, culture and the human relationship with nature and the environment. They still recognize the term customary rights. They call tanah perompai. They still considers that the forest is part of the lives of its people. Therefore, even if there are changes of forest into plantations, they still hope that the forest areas are strategic and holy places should not be tampered with in order to remain preserved. In the context of conflict resolution that is in society, the role of traditional leaders such as Temenggungs for Dayak and Penggawa's for Malay still important. Settlement of the issue resolved in stages in accordance with the large-small problem, and the complexity of the problems encountered. If complicated then used government law. However, people often use customary law by way of deliberation and consensus.